Buckling of thin-walled I-section laminated composite curved beams. (September 2020) - Huang, Sixin; Qiao, Pizhong
Abstract: The governing differential equations of thin-walled laminated composite curved beams are derived from the principle of virtual displacement. Curvature effect is fully considered, and various displacement components of curved beams are coupled. Buckling behaviors of both the laminated composite I-section vertically (with horizontal web) and horizontally (with vertical web) curved beams are studied. The characteristic displacement function for pinned-pinned curved beams is used to describe both the in-plane buckling and out-of-plane (spatial) buckling behaviors. Closed form solution for buckling analysis of I-section curved beams under compression and bending moment is obtained. Accuracy of the present closed-form solution is verified by comparing with available solutions in the literature and the numerical results of the finite element method using ABAQUS. Then, a practical application of the closed-form solution for I-section composite laminated curved beams is demonstrated, considering the placement of I-section profile, geometry of section, layup in flanges and web, and central angle. Finally, a parametric study is conducted to evaluate the effect of central angle, arc length, radius of curvature, and fiber angle of laminates on buckling behavior of I-section curved beams with either horizontal or vertical web. Highlights: Governing equations of curved beams are derived from principle of virtual displacement, with curvature and coupling effect. In-plane and out-of-plane buckling of both I-section vertically- and horizontally-curved beams are studied. Closed-form solution for buckling analysis of I-section curved beams under compression and bending moment is obtained. Effects of central angle, arc length, radius of curvature, and fiber orientation on buckling behavior are studied.